Neonatal Sweet’s syndrome associated with rectovestibular fistula with normal anus - Jun Shinozuka; Hideki Tomiyama; Shin-ichiro Tanak; Junko Tahara; Hitoshi Awaguni; Shigeru Makino; Rikken Maruyama; Shinsaku Imashuku (Pediatric Reports, 2015)
Sweet’s syndrome, characterized by fever and a painful erythematous rash with a dermal neutrophilic infiltrate, develops primarily due to paraneoplastic phenomena in adults. Sweet’s syndrome is very rare in neonates. We report a Japanese female neonate (age <2 months), who developed Sweet’s syndrome with episodes of perineal infection in association with congenital rectovestibular fistula with normal anus. Sweet’s syndrome was diagnosed basing on clinical features and histopathology of biopsied skin tissues. Rectovestibular fistula was confirmed after the signs of inflammation subsided and the rash disappeared. In the literature, we found another case of neonatal Sweet’s syndrome associated with rectovestibular fistula in a Japanese female neonate. The perineal region should be screened for anomalies following diagnosis of Sweet’s syndrome in neonates.